The Effect of Company Size, Good Corporate Governance Mechanism and Brand Name Audits On Financial Reports Integrity (Empirical Study of Basic Materials Sector Companies Listed on the IDX in 2018-2021) - Yusup Hari Subagya; Timotius Adi Setiyanto (Nur Science Institute, 2022)
The purpose of this study was to determine the effect of firm size, good corporate governance mechanisms and brand name audits on the integrity of financial statements. The mechanism of good corporate governance in this study is proxied by the audit committee and independent commissioners. Meanwhile, the integrity of financial statements is proxied by accounting conservatism. The population in this study are basic materials manufacturing companies listed on the Indonesia Stock Exchange. The number of companies sampled in this study were 40 companies with 4 years of observation. Based on the purposive sampling method, the total sample of the study was 160 financial statements and annual reports. The data collection method used is secondary data, obtained by researchers from www.idx.co.id and hypothesis testing in this study using multiple regression analysis methods. The results of this study indicate that company size and audit brand name have a positive effect on accounting conservatism, audit committees have a negative effect on accounting conservatism, and independent commissioners have no effect on accounting conservatism.